2016
DOI: 10.1063/1.4966060
|View full text |Cite
|
Sign up to set email alerts
|

The impact of knowledge sharing through social media among academia

Abstract: The world of research require researcher, academia and lecturers to share knowledge among them. With the invention of social media, knowledge sharing process has been more effective and easy. Previously, there were numerous researches done to investigate the effect of social media utilization for public used. There were also study that aimed to study social media effects in educatioanal sector but those study were centered around student's perspective. Less consideration is given towards academia's perspective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Furthermore, researchers have argued that only 11 per cent of qualitative studies across the world have examined the link between social media and knowledge sharing (Ahmed et al, 2018). Furthermore, researchers have indicated that it is rare to finder search that explores the role of social networking applications in the context of academia (Ghazali et al, 2016). An exploration of different aspects of social media is ultimately beneficial to increase knowledge sharing in university research cultures.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, researchers have argued that only 11 per cent of qualitative studies across the world have examined the link between social media and knowledge sharing (Ahmed et al, 2018). Furthermore, researchers have indicated that it is rare to finder search that explores the role of social networking applications in the context of academia (Ghazali et al, 2016). An exploration of different aspects of social media is ultimately beneficial to increase knowledge sharing in university research cultures.…”
Section: Introductionmentioning
confidence: 99%
“…This research aims to highlight how SN apps can be used efficiently and effectively to support the antecedents of KS among employees at public and private universities. Most previous studies have been conducted with a view to examining the links between SN applications and KS parties in the context of a systematic literature review (Ahmed et al , 2018; Panahi et al , 2013; Ghazali et al , 2016), using a qualitative approach (Jarrahi and Sawyer, 2013; Kotlarsky and Oshri, 2005). However, there is scant literature available in which statistical techniques have been used to generalize results to a larger population in the context of SN tools and their role in supporting the antecedents of KS practices.…”
Section: Introductionmentioning
confidence: 99%
“…Sharing material and works is an integral part of academic life and the research cycle and scholars often use social media to this end (Ghazali, et al, 2016), with three quarters of them frequently sharing material online (Elsayed, 2016). An increasing number of academics are honing their profiles on SNS to serve as digital portfolios showcasing their research findings (Segado-Boj, et al, 2015) and to enhance the visibility of their research output (Thelwall and Kousha, 2015) even farther than the traditional readers of academic journals (Knight and Kaye, 2016).…”
Section: Introductionmentioning
confidence: 99%